Literature Study: Utilization and Effective Management of School Operational Assistance (SOA) Funds - Fitri, Yusriani; Marlina, Rina; Yelfianita, Yelfianita; Marsidin, Sufyarma; Rifma, Rifma (Postgraduate School, Universitas Negeri Padang, 2024)
The distribution of School Operational Assistance (SOA) funds by the government has so far not been able to fully overcome existing education problems. Ironically, the misuse and ineffective allocation of SOA funds adds to new problems. To prevent ineffective use of SOA funds, school principals are required to be competent as managers in the process of planning, organizing, determining direction, monitoring, and providing information in the form of financial reports. The method used in this research is literature study, namely the collection and analysis of information published in books and journals that are relevant and support the research topic and other written sources. Financial management in an educational institution aims to increase the effectiveness and efficiency of financial use, increase financial accountability and transparency, and reduce misuse of the education budget. To achieve effective results, the application of management principles in managing SOA funds is very important, namely planning, organizing, implementing, and controlling. Technical guidelines for the use of regular SOA funds must be carried out based on the principles of flexibility, effectiveness, efficiency, accountability, and transparency. Therefore, applying management principles in managing SOA funds is a crucial step to ensure that these funds are used optimally and on target to support improving the quality of education.